Visceral adipose tissue in the lesser omentum predicts lymphovascular invasion, perineural invasion and survival in gastric cancer - Liu, Ping-ping; Liu, Le; Xie, Han-bing; Zhao, Lin; Pang, Shuo; Zhou, Rui-han; Wang, Shu-rui; Miao, Shi-di; Wang, Rui-tao; Fu, Shuang (Frontiers in Oncology, 2025)
BackgroundVisceral adipose tissue is associated with clinical outcomes in patients with cancer. This study aimed to investigate the relationship between preoperative visceral adipose tissue in the lesser omentum and clinical prognosis, as well as lymphovascular invasion (LVI) and perineural invasion (PNI), in patients with gastric cancer (GC).Patients and methodsA total of 943 GC patients who underwent radical surgery across three centers in China were included in the study. The patients were divided into one main cohort (center 1) consisting of 389 cases for the primary set and 165 cases for the internal validation set, as well as two external validation cohorts. Preoperative visceral fat area (VFA) in the lesser omentum was measured through radiological assessments using standard computed tomography. Survival analysis was conducted using Kaplan-Meier plots and Cox proportional risk regression models. Additionally, logistic regression analysis was utilized to identify independent risk factors for LVI and PNI in GC.ResultsPatients with low VFA in the lesser omentum (VFA-lesser omentum) exhibited shorter overall survival compared to those with high VFA-lesser omentum [training set: hazard ratio 0.791, 95% CI 0.665-0.941, p = 0.008; validation set: hazard ratio 0.882, 95% CI 0.792-0.982, p = 0.022]. Furthermore, reduced VFA-lesser omentum was an independent risk factor for LVI (odds ratio [OR] 0.917, 95% CI 0.860-0.978, p = 0.008) and PNI (OR 0.933, 95% CI 0.878-0.990, p = 0.023). The results were confirmed in the internal and external validation sets (both p < 0.05).ConclusionPreoperative VFA-lesser omentum was associated with PNI and LVI. In addition, reduced VFA-lesser omentum predicts poor survival in GC patients.